Five-Year-Old Boy With Behavioral Changes and Papilledema. Issue 1 (March 2018) - Ram, Radha; Jones, Jeremy Y.; Mohila, Carrie A.; Shah, Veeral S.
Abstract : Abstract: A 5-year-old boy had initial symptoms of behavioral changes, nausea, vomiting, headache, weight loss, and progressive vision failure. Brain MRI revealed abnormal signal intensity in both optic nerves, the optic chiasm, the right medial temporal lobe, and tissues surrounding the right supraclinoid internal carotid artery with associated leptomeningeal and spinal cord enhancement. After nondiagnostic dural and spinal arachnoid biopsies, a temporal lobe biopsy was diagnostic for a rare malignant peripheral nerve sheath tumor.